Allium stamatiadae, a new species of A. sect. Codonoprasum (Amaryllidaceae) from Andros island (Aegean Archipelago, Greece) - Trigas, Panayiotis; Bareka, Pepy (Phytotaxa, 2020)
Allium stamatiadae from Andros island (Cyclades, Aegean archipelago, Greece) is described and illustrated. It belongs to A. sect. Codonoprasum, and its closest relatives are A. orestis, a local endemic species of southern Peloponnese (Greece) and A. dirphianum, another local species from Evvia island (West Aegean, Greece). The new species grows in the understorey of riparian forests and is currently known from two localities. The chromosome number of A. stamatiadae, 2n = 2x = 16, is reported and a metaphase plate is illustrated.